Enzymatic (2R, 4R)‐Pentanediol Synthesis – "Putting a Bottle on the Table". Issue 4 (13th January 2023) - Sehl, Torsten; Seibt, Lisa; Kappauf, Katrin; Ergezinger, Pia; Spöring, Jan-Dirk; Mielke, Kristina; Doeker, Moritz; Verma, Neha; Bocola, Marco; Daußmann, Thomas; Chen, Haibin; Shi, Shumin; et al.
Abstract: (2 R, 4 R )‐Pentanediol is an interesting precursor for the synthesis of chiral ligands. A ketoreductase (KRED) was employed for the asymmetric reduction of acetylacetone to this diol. Biocatalysis often suffers from low concentrations of hydrophobic substrates and low stability of the enzyme in unconventional media. Here, we present an engineered KRED variant applicable in a neat substrate system, including upscaling to the multi‐liter scale and downstream processing (DSP). Our engineered KRED applied in a neat substrate system is a powerful technique for the synthesis of chiral diols yielding product concentrations of 208 g L −1 . Abstract : Chiral diols are interesting molecules with a diverse range of applications. In this work, we present an engineered ketoreductase used for the asymmetric synthesis of (2 R, 4 R )‐pentanediol from cheap and readily available starting materials at a 10 L scale in neat substrate conditions including downstream processing.